2011
DOI: 10.1002/hup.1230
|View full text |Cite
|
Sign up to set email alerts
|

Acute glucocorticoid effects on the multicomponent model of working memory

Abstract: Thus, hydrocortisone acutely impairs various components of working memory, including executive functioning. This effect must be considered when administering similar drugs, which are widely used for the treatment of many clinical disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…Such a finding was not observed when patients were compared according to the mean daily hydrocortisone dose. A previous study demonstrated that acute glucocorticoid administration negatively affects the different components of working memory, including executive functions (28). The positive correlation found in our study between total hydrocortisone dose and the Benton score supports this.…”
Section: Discussionsupporting
confidence: 90%
“…Such a finding was not observed when patients were compared according to the mean daily hydrocortisone dose. A previous study demonstrated that acute glucocorticoid administration negatively affects the different components of working memory, including executive functions (28). The positive correlation found in our study between total hydrocortisone dose and the Benton score supports this.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, as noted earlier, evidence from both rodents and humans suggests that glucocorticoid elevation can impair memory performance. In addition, in humans, this impairment has been seen with particular consistency for working memory as assessed with the Digit Span test (Elzinga and Roelofs, 2005; Schoofs et al, 2009; Vaz et al, 2011; Wolf et al, 2001). Thus, it is possible that postnatal glucocorticoid treatment of children with CAH may compromise their working memory ability.…”
Section: Discussionmentioning
confidence: 99%
“…Although glucocorticoid administration may not affect all working memory-related tasks (Vaz et al, 2011), one working memory task that has been found to be influenced in a number of studies is Digit Span, a task that requires the recall and recitation of strings of numbers both forwards and backwards. Studies of healthy young men have found impaired Digit Span performance following treatment-induced glucocorticoid elevations (Vaz et al, 2011; Wolf et al, 2001), as well as following stress-induced glucocorticoid elevations (Schoofs et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual-task performance-the ability to perform simultaneously two tasks that load on different storage domains-also constitutes a separable type of executive function (see Logie et al, 2004), as does planning, or the ability to organize behavior toward a specific goal that must be achieved through intermediate stages (Jurado and Rosselli, 2007;Oosterman et al, 2013), and the efficiency of access to long-term memory (see Fisk and Sharp, 2004). Updating, shifting and inhibiting are correlated but distinguishable abilities (see Miyake et al, 2000;Friedman and Miyake, 2004;Miyake and Friedman, 2012), and all six types of executive functions can be assessed separately in the same experimental setting (e.g., see Vaz et al, 2011;Ginani et al, 2011;Borges et al, 2013). Evaluation of one's own performance (metacognition) is also related to executive control (e.g., Fernandez-Duque et al, 2000) and has been little investigated in the caffeine literature.…”
Section: Introductionmentioning
confidence: 99%